EURÍPIDES E AS TROIANAS - Schell, Denis (Organon, 2012)
The work analises an Euripedes’play placing it in a significant set of drama works. It resumespoetic approaches with other important works of Esquilo. The transformation of the mith and itsmodernization appear in a process of world order change and in the presence of new conceptions of theplaywright literary work. Besides, the use of retoric resources of the poetic language and changes in aconception of the responsability of the action show, in a tragedy, a crescent process of individualization ofthe age thought.